Hubungan Peran Keluarga Dengan Kepatuhan Minum Obat Pada Klien Skizofrenia Di Poli Klinik Jiwa RSJ Tampan Provinsi Riau - Gasril, Pratiwi; Ghulam Akbar, Muhammad (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2021)
Schizophrenia is a disease that affects the brain and causes thoughts, perceptions, emotions, movements, and unnatural behavior. The causative factor of schizophrenia is caused by psychological pressure both external and individual pressure. The role of the family is very important in the treatment of schizophrenia patients. in general, schizophrenia clients have not been able to set a schedule for drug consumption, and do not know the type of drug to be taken. This study aims to determine the relationship of the role of the family with adherence to take medication in schizophrenic clients in Tampan RSJ Policlin Pekanbaru. This research is an analytic survey research and uses a cross sectional approach to see the relationship of family roles to adherence to taking medication in schizophrenic clients using quantitative methods. Based on the chi square statistical test results obtained p value = 0.001, which means there is a significant relationship between the role of the family with adherence to take medication in schizophrenia patients in the mental clinic at the Tampan Mental Hospital, Riau Province in 2019.